Worst maximum credible accidental scenarios (WMCAS) - A new methodology to identify accident scenarios for risk assessment. (July 2017) - Zhang, Feng; Zhao, Guili; Wang, Zheng; Yuan, Jiwu; Cheng, Yunfei
Abstract: The identification of accident scenarios is the key step for risk assessment in process industries. In this paper, the methodology of worst maximum credible accidental scenarios (WMCAS) was put forward based on the analysis of the existing accident scenarios (the worst accident scenarios (WAS), the maximum-credible accident scenarios (MAS) and reference accident scenarios (RAS)). The principle and procedure of WMCAS identification have also been established. Firstly, WAS can be determined based on the Methodology for the Identification of Major Accident Hazards (MIMAH) used in the frame of the Accidental Risk Assessment Methodology for Industries (ARAMIS) project. Secondly, the modified method of credibility factor in MAS is used to calculate the credibility of WAS. Finally, the WMCAS will be identified by comparing the modified credibility results of WAS. Simultaneously, a pulverized coal gasification device was selected as an illustrative example to show the application of the methodology of WMCAS. The results show that the WMCAS for the device are pool fire for the methanol vessel, mechanical explosion for the gasification furnace, vapour cloud explosion (VCE) for the scrubber and VCE for the carbon dioxide absorption tower. Highlights: A new methodology WMCAS was put forward to identify accidental scenarios for risk assessment. All potential worst accident scenarios were identified with MIMAH method. Credibility factor (A, B, C) presented by Khan was modified and calculated for every worst accident scenario. The industrial application shows WMCAS methodology is consistent and applicable.